Long-term patient-reported neurocognitive and functional outcomes after tick-borne encephalitis: a prospective controlled multicenter cohort study - Hilde Skudal; Åslaug Rudjord Lorentzen; Tore Stenstad; Else Quist-Paulsen; Børre Fevang; Keson Jaioun; Malin Veje; Hege Kersten; Randi Eikeland; Jens Egeland (Journal of Neurology, 2026)
Abstract Objective To characterize cognitive symptoms the first year after tick-borne encephalitis (TBE). Methods We conducted a controlled, multicenter cohort study of 109 hospitalized patients ≥16 years with confirmed TBE in Norway. At 3 and 12 months after admission, patients completed BRIEF-A (Global Executive Composite (GEC) and subscales), Everyday Memory Questionnaire-Revised (EMQ-R), and Rivermead Post-Concussion Symptoms Questionnaire (RPQ), assessing executive functioning, memory, and post-TBE symptoms (higher scores indicate more difficulties). The primary outcomes were within-patient change in questionnaire scores from 3 to 12 months, and 12-month scores in patients compared to controls. The secondary outcomes were BRIEF-A subscale scores and proportion with clinically significant impairment. Covariates included in the analyses were age, sex, comorbidities, acute disease severity, anxiety, and depression. Results There were no significant changes from 3 to 12 months. At 12 months, scores were within the normal range, but patients had higher EMQ-R and RPQ than controls ( p